Particulate matter distribution in selected Portuguese archives: a preliminary study - Pinheiro, Ana Catarina (2014)
Particulate matter (PM) can have a significant impact on human health and on artifacts stored and kept inside museums and archives. To the author's knowledge, its immediate and/or longterm concentrations and distribution on Portuguese archives has never been determined. Four Portuguese archives (with and without HVAC/air filtration systems) were selected and the immediate concentration of airborne particulate matter was measured by active sampling. Indoor-outdoor ratios were also determined. International and national guidelines were used to ascertain the environment’s quality, both for the readers and staff and for the documents preserved in these institutions. Inside, PM2.5 ranged between 0.37μg/m3 and 27.61μg/m3, while PM10 ranged between 4.43μg/m3 and 285.52μg/m3. The lowest values were determined in storage rooms and the highest in reading rooms. In terms of human health, Portuguese guidelines for immediate PM10 concentration were not met in several locations. For conservation purposes, storage rooms were classified according to an original air quality grid. Air filtration systems proved valuable in maintaining a safe environment for our written heritage and the staff and readers that deal with it and care for it every day. This study constitutes the first snapshot of the particulate matter concentrations and distribution in Portuguese Archives.